Case Study: Analysis of the Effect of Food Texture on Baby’s Language Acquisition - Fitri Ayu (MultiTech Publisher, 2023)
This research was purposed to analyze the effect of baby’s food texture on baby’s language acquisition. The method used in this research was qualitative method especially case study on two babies who are siblings. This research was focused on their language acquisition when their age was 9-24 months. The data earned was primary data from the mother and her children Au and Mu through interview, observation and diary notes. The result of this research showed that the food texture brought many effects of baby’s language acquisition.